Pulmonary Artery to Left Atrium Fistula Presenting As Cardiomegaly in the Fetus: The Utility of Prenatal and Postnatal Three-Dimensional Imaging. (August 2019) - Kehr, Jascha; Stirling, John W.; Bagnall, Carol; Long, Audrey; Artrip, John H.; Gentles, Thomas L.
Abstract : Supplemental Digital Content is available in the text.